First detection and molecular characterization of sapoviruses and noroviruses with zoonotic potential in swine in Ethiopia - Sisay, Z.; Djikeng, Appolinaire; Berhe, N.; Belay, G.; Abegaz, W.E.; Wang, Q.H.; Saif, L.J. (Springer, 2016)
Noroviruses (NoVs) and sapoviruses (SaVs), which belong to the family Caliciviridae, are important human and animal enteric pathogens with zoonotic potential. In Ethiopia, no study has been done on the epidemiology of animal NoVs and SaVs. The aim of this study was to detect and characterize NoVs and SaVs from swine of various ages. Swine fecal samples (n = 117) were collected from commercial farms in Ethiopia. The samples were screened for caliciviruses by reverse transcription polymerase chain reaction (RT-PCR) using universal and genogroup-specific primer pairs. Phylogenetic analysis was conducted using a portion of the RNA-dependent RNA polymerase (RdRp) region and the VP1 region of genome sequences of caliciviruses. Among 117 samples, potential caliciviruses were detected by RT-PCR in 17 samples (14.5 %). Of the RT-PCR-positive fecal samples, four were sequenced, of which two were identified as human NoV GII.1 and the other two as porcine SaV GIII. The porcine SaV strains that were detected were genetically related to the porcine enteric calicivirus Cowden strain genogroup III (GIII), which is the prototype porcine SaV strain. No porcine NoVs were detected. Our results showed the presence of NoVs in swine that are most similar to human strains. These findings have important implications for NoV epidemiology and food safety. Therefore, continued surveillance of NoVs in swine is needed to define their zoonotic potential, epidemiology and public and animal health impact. This is the first study to investigate enteric caliciviruses (noroviruses and sapoviruses) in swine in Ethiopia.